2020
DOI: 10.1007/s11705-020-2003-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydrophobicity: effect of alkyl chain length and network homogeneity

Abstract: Understanding the nature of hydrophobicity has fundamental importance in environmental applications. Using spherical silica nanoparticles (diameter = 369 ± 7 nm) as the model material, the current study investigates the relationship between the alkyl chain network and hydro-phobicity. Two alkyl silanes with different chain length (triethoxymethylsilane (C1) vs. trimethoxy(octyl)silane (C8)) were utilised separately for the functionalisation of the nanoparticles. Water contact angle and inverse gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The longer the chain, the more hydrophobic the surface. Similar results were obtained by Chen et al (2021) when investigating the effect of silane chain length on the hydrophobicity of spherical silica nanoparticles. They showed that the alkyl chain length was essential for controlling the hydrophobicity (wettability).…”
Section: Surface Wettabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…The longer the chain, the more hydrophobic the surface. Similar results were obtained by Chen et al (2021) when investigating the effect of silane chain length on the hydrophobicity of spherical silica nanoparticles. They showed that the alkyl chain length was essential for controlling the hydrophobicity (wettability).…”
Section: Surface Wettabilitysupporting
confidence: 84%
“…Such drop covers a relatively large area of the sample compared to the size of the -OH groups and hydrocarbon chains. As the chain length of the alcohol used for esterification increases, the -OH groups remaining on the surface are increasingly shielded by the chains (Chen et al, 2021). When the measurement is carried out by inverse gas chromatography (iGC), the probe molecules can directly interact with the functional groups on the surface, in this case -OH groups.…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…The WCAs were found to be larger when the chain length increased from C6 to C12 regardless of a lower grafting density. These results pointed out that it is easier for a longer alkyl chain to shield the surface from water by forming a hydrophobic network [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alkyl chain length has a positive effect on the hydrophobicity of the materials. The longer alkyl chain provides a better shield from the water than the smaller alkyl chains [ 43 ].…”
Section: Resultsmentioning
confidence: 99%